2015
DOI: 10.1016/j.trc.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

A hyperpath-based network generalized extreme-value model for route choice under uncertainties

Abstract: Previous route choice studies treated uncertainties as randomness; however, it is argued that other uncertainties exist beyond random e↵ects. As a general modeling framework for route choice under uncertainties, this paper presents a model of route choice that incorporates hyperpath and network generalized extreme-value-based link choice models. Accounting for the travel time uncertainty, numerical studies of specified models within the proposed framework are conducted. The modeling framework may be helpful in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…There are many future research possibilities that have been pointed out in the paper: (a) creating optimal static TWM distributions for historical data with evolutionary algorithms, (b) creating dynamic traffic assignment models using TWM based on previous driver experiences as we have shown that they may be critical for TWM adherence, (c) using TWM for zone routing policies as pointed by [49], (d) applying TWM to hyperpath calculation using techniques described by [12,34], (e) creating evolutionary algorithms and optimization functions for finding local area minimum for routing maps that can cover eventual time-dependent situations, and (f) extension of the MuTraff MTS simulator with mesoscopic simulation engines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many future research possibilities that have been pointed out in the paper: (a) creating optimal static TWM distributions for historical data with evolutionary algorithms, (b) creating dynamic traffic assignment models using TWM based on previous driver experiences as we have shown that they may be critical for TWM adherence, (c) using TWM for zone routing policies as pointed by [49], (d) applying TWM to hyperpath calculation using techniques described by [12,34], (e) creating evolutionary algorithms and optimization functions for finding local area minimum for routing maps that can cover eventual time-dependent situations, and (f) extension of the MuTraff MTS simulator with mesoscopic simulation engines.…”
Section: Discussionmentioning
confidence: 99%
“…The hyperpath routing approach addresses uncertainty and variability of traffic dynamics, where individual traffic agents receive for each origin and destination a tree of alternatives, as opposed to a single route [10,11,13,32]. It feeds off historical data to discern traffic behavior patterns [12,33,34], thus requiring heavy back-end computing to synthesize the pre-trips. TWM is complementary to hyperpaths as it provides different network views for hyperpath calculation.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…TWM is fully compatible with the hyper-path concept, where individual traffic agents receive for each origin and destination not a single route but a tree of alternatives [11], [23], [34], [41]. Hyper-path route calculus considers the uncertainty and variability of traffic dynamics, and uses mainly historical data as traffic behavior patterns where different analysis methods can be applied [19], [29], [33]. Hyper-path calculus to synthesize the pre-trips require a lot of back-end computing while receiving data streaming for the network and the mobile agents, and also en-route distribution is required to the distribution servers.…”
Section: A Backgroundmentioning
confidence: 99%
“…Second, the RPSS was developed to find a priori α‐reliable path for travellers in face of travel time uncertainties. In the literature, substantial attentions also have been given to adaptive en‐route guidance applications for finding a set of routing strategies when the en‐route traffic information are updated during journeys (Fan and Nie, ; Bell, ; Ma et al , , Ma and Fukuda, ). How to extend the proposed ERSP‐A* algorithm to the adaptive en‐route guidance applications is another interesting topic of further studies.…”
Section: Discussionmentioning
confidence: 99%